Pengaruh ovaprim, aromatase inhibitor, dan hipofisa terhadap kualitas telur ikan Lele Dumbo (Clarias gariepinus) - Aziz, Erwin A.; Kalesaran, Ockstan (Universitas Sam Ratulangi, 2017)
This study aimed to determine the effect of ovaprim hormone, aromatase inhibitor and pituitary on the quality of the catfish eggs (Clarias gariepinus). Experimental Design used was Completely Randomized Design (CRD) with four treatments, each with three replications. Treatment A: ovaprim; treatment B: Aromatase inhibitors, treatment C: hypophysis and treatment D: Control. The results showed that the difference in treatment gave highly significant effect on fertilization and hatching eggs but no significant effect on the survival rate of larvae. Aromatase inhibitor hormone was the best because it provided highly significant effect on fertilization (92.66%), hatchability of eggs (95%), and surviva rate (81.33%) of fish larvae. Â Keywords : Clarias gariepinus. Ovaprim, Aromatase Inhibitor, Hypophysis, egg, larvae